2012
DOI: 10.1158/1078-0432.ccr-11-2059
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Temozolomide in Patients with Relapsed Sensitive or Refractory Small Cell Lung Cancer, with Assessment of Methylguanine-DNA Methyltransferase as a Potential Biomarker

Abstract: Purpose: This phase II study was conducted to assess the efficacy of temozolomide in patients with relapsed small cell lung cancer (SCLC).Experimental Design: Patients with disease progression after one or two prior chemotherapy regimens received temozolomide at 75 mg/m 2 /d for 21 days of a 28-day cycle. The primary endpoint was the overall response rate [ORR; complete response (CR) plus partial response (PR)], which was evaluated separately in sensitive and refractory cohorts. In the available tissue, we ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
113
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 26 publications
2
113
1
1
Order By: Relevance
“…While the objective response rates were similar to those demonstrated in our study-23% (11/48) in patients with platinum-sensitive disease and 13% (2/16) in patients with platinum-refractory disease-the median duration of response to temozolomide was lower: 3·5 months (range, 1·4-14·7 months) for all treated patients. 26 A newer agent, Rova-T, a DLL3 targeted antibody drug conjugate, demonstrated anti-tumour activity and manageable toxicity in a phase 1 study of patients with SCLC and progression after one or two previous lines of therapy. 27 The objective response rate was 44% (7/16) in patients positive for the DLL3 biomarker treated at the maximum tolerated doses.…”
Section: Discussionmentioning
confidence: 99%
“…While the objective response rates were similar to those demonstrated in our study-23% (11/48) in patients with platinum-sensitive disease and 13% (2/16) in patients with platinum-refractory disease-the median duration of response to temozolomide was lower: 3·5 months (range, 1·4-14·7 months) for all treated patients. 26 A newer agent, Rova-T, a DLL3 targeted antibody drug conjugate, demonstrated anti-tumour activity and manageable toxicity in a phase 1 study of patients with SCLC and progression after one or two previous lines of therapy. 27 The objective response rate was 44% (7/16) in patients positive for the DLL3 biomarker treated at the maximum tolerated doses.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigated temozolomide in patients with small cell lung cancer without selection for MGMT methylation status (51). The RRs for chemotherapy-sensitive and refractory cases were 23% and 13%, respectively, in this relatively homogeneous population.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].5% (1,2). Temozolomide, a chemotherapeutic drug, is a suitable option for relapsed SCLC, particularly when brain metastases are present (3,4), and it has been recommended for second-line treatment of SCLC in the National Comprehensive Cancer Network guidelines (5). In a phase II study of the efficacy of temozolomide in the treatment of SCLC, Pietanza et al (3) established the methylation status of the O 6 -methyl-guanine-DNA methyltransferase (MGMT) promoter in 27 patients, and found that the overall promoter methylation rate in those patients was 48%.…”
Section: Introductionmentioning
confidence: 99%
“…A significantly greater proportion of cases with methylated MGMT exhibited a response to temozolomide compared with those with unmethylated MGMT (38 vs. 7%; P=0.08). These results suggest that the response to temozolomide treatment may be associated with the MGMT methylation status in SCLC (3). Temozolomide administered at a dose of 200 mg/m 2 /day for 5 days in 28-day cycles is tolerable and active in patients with relapsed SCLC (4).…”
Section: Introductionmentioning
confidence: 99%